Optimization of a cryopreservation protocol for a Malaysian fresh water micro algal, Chlorella vulgaris / Nor Afiqah Anua (2016)
Microalgae is important in many biotechnological exploitations in producing valuable products, services and processes. Many microalgal strains are able to grow post cryopreservation because the technology of cryopreservation has improved tremendously over the years. Cryopreservation is a process whereby the cells or the whole tissue are preserved by cooling to an ultralow temperature of -196°C such that it remains capable of growth upon thawing. In this study, Chlorella vulgaris was used to determine the viability post cryopreservation at different concentrations of cryoprotectant employing three different protocols. Dimethyl sulfoxide (DMSO) at different concentrations of 0%, 10%, 20% and 30% were added to the microalgal suspension in the research. Protocol 1 involves direct plunging into liquid nitrogen, Protocol 2 is slow cooling to -80°C and Protocol 3 is slow cooling to -20°C. The absorbance value at 540 nm was used as a measurement to determine the growth post cryopreservation. The absorbance value recorded with 30% DMSO in Protocol 2 showed the highest at 0.387 ± 0.015 and was significant at p<0.05 compared to Protocol 1 and 3. The best protocol for the optimization of the cryopreservation of C. vulgaris was Protocol 2 using slow cooling to -80 °C treated with 30% DMSO as the cryoprotective agent.